Investigation of mec A gene of Staphylococcus aureus causing Mastitis - كاظم حميد, سميرة; باسم رسول الدباغ, ميادة (University of Thi-Qar Journal of Science, 2016)
128 of pus samples were collected from women's infected with Mastitis. The identification of the Staphylococcus aureus isolates depended on colonial morphology, microscopic examination and biochemical tests as a primary identification, and detection of found mec A gene using the polymerase chain reaction. The researches to the following results:The results showed that 22 isolates did not appear any growth and percentage (17.19)% whereas 106 (82.81%) isolates belongs to Staphylococcus and 34 from this isolates belongs to Staphylococcus aureus and percentage (32.07)% the research has detected the presence of genetic factor mec A belongs to Staphylococcus aureus (34) where the number of the samples carrying the gene 14 (41.1%).The results also includes a high association between this genetic factor and Methicillin Resistant Staphylococcus aureus (MRSA). Besides, there is also a correlation between MRSA and Mastitis diseases. This study draws attention to the current increase in MRSA in Najaf city which increases the importance of working to develop means of infection control to prevent further spread in the community.